MANAJEMEN BERBASIS SEKOLAH PADA MTSN MODEL BANDA ACEH - aishah .; Yusrizal .; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
School based management as a practical approach whose aim is to design and to manage the school system by giving power to the school principal  and increase teachers participation, parents and society. MBS is expected to improve the quality of sustainable and having independence. This study aims to know the application of MBS in MTsN Model Banda Aceh. Approach research used is a qualitative approach. Method of this research is descriptive with data collection by using  observation, interviews and documentation. Research subjects are principals, deputy of curricula, students’ affairs, public relations and teacher.  The result of the research shows that: (1) curriculum field management discuss preparation of learning, comprehension, mastery of teaching material competence / subject matter and purpose; Use of forms in classroom management, using methods and learning with media. (2) Student field management develops the potential of learners optimally integrated, including; Talent, interest and creativity. (3) Personnel management on MTsN Model of teacher development, providing self-development opportunities and recruitment of companion teachers. (4) Community relationship management functions, among others, fostering school relationships with parents. Maintain good relationships with school committees. School relations with the community were built with the aim of popularity of MTsN Model in the community.Keywords:  school based management, principal, work program.